Characterization of Arabidopsis thaliana R2R3 S23 MYB Transcription Factors as Novel Targets of the Ubiquitin Proteasome-Pathway and Regulators of Salt Stress and Abscisic Acid Response - Beathard, Chase; Mooney, Sutton; Al-Saharin, Raed; Goyer, Aymeric; Hellmann, Hanjo (Frontiers in Plant Science, 2021)
Rapid response to environmental changes and abiotic stress to coordinate developmental programs is critical for plants. To accomplish this, plants use the ubiquitin proteasome pathway as a flexible and efficient mechanism to control protein stability and to direct cellular reactions. Here we show that all three members of the R2R3 S23 MYB transcription factor subfamily, MYB1, MYB25, and MYB109, are degraded by the 26S proteasome, likely facilitated by a CUL3-based E3 ligase that uses MATH-BTB/POZ proteins as substrate adaptors. The work further provides a detailed description of MYB25 and MYB109 expression, shows its subcellular localization, and demonstrates that its elevated expression of MYB25 reduces sensitivities towards abscisic acid and salt stress in Arabidopsis. Transcriptional profiling of plants overexpressing MYB25 shows that the transcription factor widely affects cellular stress pathways related to biotic and abiotic stress control. Overall, the work extends our knowledge on proteins targeted by CUL3-based E3 ligases that use MATH-BTB/POZ proteins as substrate adaptors and provides first information on all members of the S23 subfamily.